Influence of land use with cocoa crops, chakras and primary forest on diversity, carbon storage and productivity in Sumaco Biosphere Reserve, Ecuador - Jadán Maza, A.O. (2012)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),2012